Two beginnings of geometry and folding: Hermann Wiener and Sundara Row. Issue 1 (2nd January 2016) - Friedman, Michael
Abstract : In this paper we examine two mathematicians who published manuscripts on geometry and origami in the same year, 1893: Hermann Wiener and Sundara Row. The main question that concerns us is to situate these works in the correct historical and mathematical background. We suggest that Wiener and Row offer us, via folding a piece of paper, a new conception of geometry that is very different to the common conception at the time.